Periodontal disease progression in subjects with orofacial clefts over a 25-year follow-up period - Huynh-Ba, Guy; Brägger, Urs; Zwahlen, Marcel; Lang, Niklaus P.; Salvi, Giovanni E. (Journal of clinical periodontology, 2009)
Aims: To assess rates of periodontal disease progression in subjects with cleft lip, alveolus and palate (CLAP) over a 25‐year period without regular maintenance care in a specialist setting and to compare those with those of subjects without alveolar clefts, i.e. cleft lip (CL) or cleft palate (CP). Material and Methods: Ten subjects with CLAP and 10 subjects with CL/CP were examined in 1979, 1987, 1993 and 2004. Probing pocket depth (PPD), clinical attachment level (CAL), bleeding on probing (BoP) and plaque control record (PCR) scores were recorded in all 20 subjects. Results: High plaque and BoP scores were recorded at all examinations in both groups. Over 25 years, a statistically significant loss of mean full‐mouth CAL of 1.52 ± 0.12 mm (SD) and 1.66 ± 0.15 mm occurred in the CLAP and CL/CP group respectively (p<0.05). A statistically significant increase (p<0.05) in mean full‐mouth PPD of 0.35 ± 0.12 mm was observed in the CL/CP group, whereas only a trend for a mean full‐mouth increase in PPD of 0.09 ± 0.11 mm was observed in the CLAP group. In subjects with CLAP, a statistically significant increase (p<0.05) in PPD of 0.92 ± 1.13 mm at cleft sites was observed compared with that of 0.17 ± 0.76 mm at control sites. With respect to CAL, the loss at the corresponding sites amounted to 2.71 ± 1.46 and to 2.27 ± 1.62 mm, respectively (p=0.36). Conclusions: When stringent and well‐defined supportive periodontal therapy was not provided, subjects with orofacial clefts were at high risk for periodontal disease progression. Over 25 years, alveolar cleft sites tended to have more periodontal tissue destruction compared with control sites.